2017
DOI: 10.1186/s12931-017-0684-9
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function, exhaled nitric oxide and symptoms in asthma patients with obesity: a cross-sectional study

Abstract: BackgroundObesity is a risk factor for the development of asthma. In patients with obesity the diagnosis of asthma is often based on symptoms, but without objective measurements. Nevertheless, obesity-associated asthma is recognized as a distinct asthma phenotype. Therefore, this study explores lung function and symptoms in asthma patients with and without obesity.MethodsThe Netherlands Epidemiology of Obesity (NEO) study is a population-based cohort study with 6671 participants (aged 45–65 years) of whom 472 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 39 publications
3
22
0
3
Order By: Relevance
“…Thus, in the prospective Netherlands Epidemiology of Obesity cohort study, high FeNO levels were observed in 25% of obese asthmatics. When compared with the remaining obese asthmatics, those with high FeNO levels had greater bronchoconstriction and more symptoms related to pollen, dust, or animal exposure, suggesting the predominance of a T H 2 pattern [35].…”
Section: Should Obesity Be Taken Into Account In the Diagnosis And Fomentioning
confidence: 92%
See 2 more Smart Citations
“…Thus, in the prospective Netherlands Epidemiology of Obesity cohort study, high FeNO levels were observed in 25% of obese asthmatics. When compared with the remaining obese asthmatics, those with high FeNO levels had greater bronchoconstriction and more symptoms related to pollen, dust, or animal exposure, suggesting the predominance of a T H 2 pattern [35].…”
Section: Should Obesity Be Taken Into Account In the Diagnosis And Fomentioning
confidence: 92%
“…In addition, we must confirm that the patient's symptoms are related to the objective presence of reversible airflow limitation, together with changes in lung volumes and bronchial hyperresponsiveness [43,47]. Obesity itself does not alter the bronchial response to methacholine in terms of FEV 1 values [24,35], thus making the methacholine challenge test especially useful in the diagnosis of asthma. However, during bronchoconstriction, obese patients without asthma develop more dyspnea [37,48,49] and air trapping than nonobese patients [50], probably as a result of greater limitation of expiratory flow and premature closure of the airways.…”
Section: Should Obesity Be Taken Into Account In the Diagnosis And Fomentioning
confidence: 99%
See 1 more Smart Citation
“…Лица, страдающие БА на фоне ожирения, испытывают на себе влияние феномена полиморбидности, что в сочетании с развитием резистентности к ингаляционным глюкокортикостероидам сопровождается ухудшением контроля течения основного заболевания, повышением частоты и длительности госпитализации [15]. Пациенты с БА, сочетанной с ожирением, имеют больше респираторных симптомов и более низкие значения объема форсированного выдоха за первую секунду (ОФВ1) и форсированной жизненной емкости легких (ФЖЕЛ) по сравнению с пациентами без ожирения [16]. Ассоциация БА и ожирения имеет гендерные и возрастзависимые особенности [17].…”
Section: фенотип бронхиальной астмы сочетанной с ожирениемunclassified
“…В то же время в исследовании M.J. Kasteleyn и соавт. не было обнаружено различий в уровне выдыхаемого NO между пациентами с БА без ожирения и пациентами, страдающими БА на фоне ожи-рения [16]. Продуцируемый NO, наряду с защитным эффектом (расслабление гладких мышц бронхов, ослабление гиперчувствительности дыхательных путей), может оказывать цитотоксическое или цитостатическое действие на клетку при определенных условиях.…”
Section: роль инсулинорезистентности во взаимосвязи бронхиальной астмunclassified